AN ANALYSIS OF THE COHERENCE OF READER’S LETTERS IN THE JAKARTA POST NEWSPAPER - Indah Wika Kusuma Wardani Pratiwi (Universitas PGRI Semarang, 2014)
The objectives of the study are: 1) to find out how coherent of the texts in reader’s letters of Jakarta post newspaper. 2) to find out the coherence markers found in the texts. 3) to find out the dominant coherence markers found in the texts.ance it just collected and analyzed the data then drew a conclusion based on the data without taking into general conclusion. The data analyzed were 5 texts of reader’s letters of Jakarta Post newspaper which published on May 2014. The instrument of this study was documentation in the form of reader’s letters texts in Jakarta Post newspaper published on May 2014.The analysis of the texts was based on the logical order and transitional signals used. The result of the analysis showed that the reader’s letter texts in the Jakarta Post newspaper have logical ideas that arranged orderly and the transitional signals used were appropriate with its function. So, it can be concluded that the texts were have good coherence. Coherence markers found in the texts were in the type of coherence relations which functioned as temporal sequence, cause-effect, similarity, condition, contrast, elaboration, example, and violated expectation. The dominant coherence markers found were the coherence markers which include in the type of temporal sequence, cause-effect, similarity, condition and contrast relation. The coherence markers make the texts more coherent because it helps to make the communication clearer for the readers. The writer has some suggestions for English lecturers and the readers. The writer suggests the English lecturers to use reader’s letter texts of English newspaper as the examples in teaching writing, especially about coherence of the texts. Moreover, the readers can use this result of the study as the reference in studying writing. Thus, the readers can make the coherence writing that readable and can be understood easily by the others